Curriculum Management to Shape Students' Competence in Knowledge, Religious Values, and Morals - Salamah, Nuris; Mujiono; Muslihun (Journal of Education and Learning Innovation, 2025)
Education is a process that makes humans better, more knowledgeable, and more skilled. The involvement of teachers and principals is very important to achieve this goal. RA Al-Aziziyah Mojokerto has high discipline as evidenced by the use of very neat uniforms, precisely when students enter and leave class according to the existing schedule, have high manners and have a social spirit. then the researcher is interested in raising the title Curriculum Management at RA Al-Aziziyah in order to form student competencies related to knowledge of religious and moral values. This study uses a qualitative type approach with 3 problem formulations, namely 1. How is curriculum management in shaping the competence of knowledge of religious and moral values  of students at RA Al-Aziziyah? 2.  How is the Management of Early Childhood Learning Environment Design at RA Al-Aziziyah Mojokerto? 3. What factors support and inhibit curriculum management in shaping the knowledge competence of religious and moral values of students at RA Al- Aziziyah? This research resulted in a finding that RA Al-Aziziyah Mojokerto has several activities that can increase students' knowledge about religious and moral values such as daily activities, spontaneous activities, exemplary activities and programmed activities, coupled with creativity in managing environmental designs to increase students' enthusiasm in learning to be one of the factors supporting success in the competence of knowledge of religious and moral values in students.